Impact of Teachers’ Emotions on the Students’ Level of Engagement. A Secondary level study - Nosheen Rehman; Dr. Muhammad Akhtar Kang; Dr. Fayyaz Ahmad Shaheen, (Dialogue Social Science Review (DSSR), 2025)
Teachers' emotions impact student participation in secondary schools. As a result, positive emotional responses from teachers dramatically increase students' attention, engagement, and participation. Negative emotions, on the other hand, might undermine student participation and lower overall classroom engagement. The study aimed to establish the association between instructors' emotions and students' levels of involvement at the secondary level. The study employed a quantitative research approach. The descriptive study comprised instructors and students from Karachi's private and public secondary schools. The researcher utilized a random sampling strategy to choose a sample of 35 instructors and 35 pupils from private and public secondary schools. The study collected data using different questionnaires for teachers and students. The data were analyzed using SPSS. The study found a strong link between instructors' emotional displays and student involvement levels. Students taught by professors who regularly expressed positive emotions reported better levels of motivation, involvement, and interest in classroom activities. Teachers who expressed negative emotions, on the other hand, were found to have a lower level of involvement. As a result, the study made valuable recommendations for policymakers, educators, and practitioners to hold frequent workshops, provide training, and design policies centered on stress management, developing good teacher-student interactions, and creating emotionally supportive classroom settings.